Design of TI-TMS system for deep brain stimulation with higher focus in neural modulation - Yanqing Zhang; Tingyu Wang; Chao Cui; Guizhi Xu (Scientific Reports)
Abstract Transcranial magnetic stimulation (TMS) is a noninvasive procedure that uses magnetic fields to stimulate neurons in the brain and has been widely applied in the field of clinical neuromodulation. However, traditional TMS has limitations in terms of focality and stimulation depth, making it unable to achieve precise modulation of deep brain regions. As the stimulation depth increases, the focal area expands, potentially stimulating nontarget regions and causing negative side effects. Moreover, strongly induced electric fields can lead to adverse effects such as seizures. Temporal interference transcranial magnetic stimulation (TI-TMS) is a novel noninvasive neuromodulation technique that has considerable potential for reducing the focal area and increasing the stimulation depth. To study the mechanisms and effects of TI-TMS, this research first established a TI-TMS simulation platform based on a five-layer spherical model. This paper designed a double curved-elliptical coil structure, increasing the stimulation depth of the TI-TMS to 5.02 cm while reducing the focal area to 18.61 cm2. Finally, a TI-TMS system was developed, with a focus on the design and development of the insulated-gate bipolar transistor (IGBT) driving circuit and the coil capacitor resonance part. The current amplitude and frequency in the coils were measured to validate the system’s effectiveness. This study confirmed that TI-TMS can effectively stimulate deep brain regions and provide new insights for the application of TMS in the rehabilitation of neurological diseases.